AIR POLLUTION IN TASHKENT CITY: PROBLEMS AND SOLUTIONS - Sultonov Erkin Yoqubjon o‘g‘li; Jalolov Nozimjon Nodir o‘g‘li (American Journals Publishing, 2024)
The 21st century is a period of accelerated urbanization processes on a global scale, and along with socio-economic growth in large cities, environmental problems are also sharply increasing. Tashkent is no exception to this process.[1] Currently, the level of urban air pollution is becoming a serious threat to the health and quality of life of the population.[2]
Keywords: Atmosphere, weather, Tashkent city, ecology.